2020
DOI: 10.7150/jca.32855
|View full text |Cite
|
Sign up to set email alerts
|

LNC00673 suppresses proliferation and metastasis of pancreatic cancer via target miR-504/ HNF1A

Abstract: Pancreatic cancer is a highly invasive malignant tumor of the digestive system. To explore the mechanism of pancreatic cancer development, development, invasion and metastasis, in this study we focused on long non-coding RNA (LncRNA), which has been reported to be involved in tumorigenesis. We identified a LINC00673, which is highly correlated with the pancreatic cancer risk. LINC00673 Overexpression is associated with good survival in pancreatic cancer patients, Effects of LINC00673 on pancreatic cancer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
(27 reference statements)
1
21
0
Order By: Relevance
“…LINC00673 expression was found to be significantly reduced in PC cells, where it functions to suppress cell invasion and migration by inhibiting miR-504 (ref. 18 ). In addition, the lncRNA PXN-AS1 was identified as a ceRNA for miR-3064 and, through miR-3064 sequestration, was found to promote the expression of the tumor suppressor PIP4K2B, resulting in the inhibition on PC progression 19 .…”
Section: Discussionmentioning
confidence: 99%
“…LINC00673 expression was found to be significantly reduced in PC cells, where it functions to suppress cell invasion and migration by inhibiting miR-504 (ref. 18 ). In addition, the lncRNA PXN-AS1 was identified as a ceRNA for miR-3064 and, through miR-3064 sequestration, was found to promote the expression of the tumor suppressor PIP4K2B, resulting in the inhibition on PC progression 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, LINC00673 is also correlated with good outcomes in PDAC patients. It can negatively regulate miR-504 to inhibit the progression of PDAC (73). There are many potential lncRNAs biomarkers that remain to be explored and translated to clinical practices.…”
Section: Meg3mentioning
confidence: 99%
“…Currently, LncRNAs act as quenchers of miRNA to regulate tumor progress 26 . For example, the proliferative, invasiveness, and migratory capacity of pancreatic cancer cell lines are regulated by LncRNA linc00673 by sequestering miR-504 27 . Previous study indicated that EIF3J-AS1 may induce HCC progression via sponging miR-122e-5p 15 .…”
Section: Discussionmentioning
confidence: 99%